2009
DOI: 10.1002/cne.22206
|View full text |Cite
|
Sign up to set email alerts
|

Decreased number of parvalbumin and cholinergic interneurons in the striatum of individuals with Tourette syndrome

Abstract: Cortico-basal ganglia neuronal ensembles bring automatic motor skills into voluntary control and integrate them into ongoing motor behavior. A 5% decrease in caudate (Cd) nucleus volume is the most consistent structural finding in the brain of patients with Tourette syndrome (TS), but the cellular abnormalities that underlie this decrease in volume are unclear. In this paper, the density of different types of interneurons and medium spiny neurons (MSNs) in the striatum was assessed in the postmortem brains of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

24
343
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 420 publications
(380 citation statements)
references
References 62 publications
24
343
1
2
Order By: Relevance
“…important, but it may manifest only in the context of other pathology, such as the deficit in parvalbumin-expressing interneurons that has also been documented in postmortem tissue (25,26), or only through its secondary effects on the functions of striatal circuits during development. Such questions cannot readily be addressed by observational studies in patients.…”
Section: Significancementioning
confidence: 99%
See 3 more Smart Citations
“…important, but it may manifest only in the context of other pathology, such as the deficit in parvalbumin-expressing interneurons that has also been documented in postmortem tissue (25,26), or only through its secondary effects on the functions of striatal circuits during development. Such questions cannot readily be addressed by observational studies in patients.…”
Section: Significancementioning
confidence: 99%
“…They are reduced by ∼50% throughout the dorsal striatum in TS (26,27). Abnormalities in ChAT interneurons in the ventral striatum have been reported in schizophrenia (28), but deficits in the dorsal striatum (the caudate and putamen) have only been described in TS (26).…”
mentioning
confidence: 98%
See 2 more Smart Citations
“…Only a small number of postmortem TS brains have been examined pathologically. Two postmortem brain studies revealed a decrease in parvalbumin positive GABA neurons and cholinergic neurons in the striatum [6,7]. Further support for a disturbance of GABA neurotransmission comes from a recent positron emission tomography study that found abnormal binding of GABA A receptor binding in patients with TS compared to normal controls [8].…”
Section: Pathogenesismentioning
confidence: 99%